Analisis Manajemen Risiko Sistem Informasi Manajemen Rumah Sakit (SIMRS) dengan ISO 31000 Pada Rumah Sakit XYZ PEKANBARU - Dwi Erlangga; Mona Fronita; Eki Saputra; M Megawati; Arif Marsal (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research aims to find out what risks may occur at xyz hospital Pekan Baru and how big the probability is and the impact on xyz hospital, by using ISO 31000 and determining the RACI Chart. The first step is risk assessment. It consists of the phases of risk identification, risk analysis, and risk assessment. In the second stage, risk treatment is used. In this phase, we will solve any solutions that will reduce or even prevent all the consequences and potential damage that may occur due to the risk. The findings of this research are that there are 10 risks, 2 of which are in the High category and 8 of which are in the Medium category, the risk treatment for the High category needs to be taken seriously where the risk treatment for power outages has a UPS (backs up computer power when the power goes out) and then connected to generators, and risk treatment for fire. Providing fire extinguishers at every point in the hospital, and there is a code red team (front guard team in case of fire). 2 risks, namely fire and power outages, which are classified in the high category and require serious action to handle them, and there are 8 medium risk categories, at the medium level the number that appears the most is number 12 where there are 4 risks, namely server down, human error , lightning, and corrupt data which has the number 12 and the number 12 also needs to take serious action to deal with it because it is almost classified as High.